The reproductive responses of two breeds of beef cows and the performance of their progeny in two contrasting environments - Niekerk, A. van; Lishman, A.W; Lesch, S.F. (1986)
The experiment was carried out over three seasons during which a total of 889 Afrikander and 805 Simmental 'cow years' were studied. Nucleus breeding herds of each of these breeds were maintained at stations in the Highland Sourveld and the Valley Thornveld. At weaning, half of the progeny of each breed were transferred to the alternate location; the other half were retained at their original location. Afrikander and Simmental cows had calving rates of 53.59% and 58.85% respectively in the Thornveld and 65.82% and 76.24% in the Sourveld. Significantly more Afrikander (44%) and Simmental (21%) calves were weaned in the Thornveld than the Sourveld. Breed and feed situation (stalls vs. veld) had a highly significant effect (P < 0.01) on ADG from weaning to final mass. Both the Simmental and the Afrikander calves consumed significantly more DM/kg gain in the Sourveld, than their counterparts in the Thornveld.